AFCA: the first foothill between Australia's Twin Peaks. Issue 4 (1st October 2020) - Schmulow, Andrew; Virginia, Dore; Jacob, Reardon; William, Hanna
Abstract : This paper traces the establishment of the new Australian Financial Complaints Authority (AFCA). It places this development within the wider context of what we argue is an important new adjunct to the Australian financial regulatory architecture, and by implication therefore, the international significance of these reforms to countries that have adopted the Australian "Twin Peaks" model. By reference to the Ramsay Review and other sources, we include analysis of AFCA's forerunners, and their failures; and we include comparative analysis from other jurisdictions. We provide analysis of AFCA's strengths and potential weaknesses, and some initial data on AFCA outcomes. Finally, we provide concluding remarks on these reforms.